CORRUPTION AND WELFARE: A SIMPLE ECONOMETRIC ACROSS COUNTRIES ANALYSIS - Joko Mariyono (Universitas Islam Indonesia, 2012)
The objective of this study is to measure the impact of corruption on welfare, and to compare the magnitude of impact between high-income and low-income countries. Corruption perception index is used as a proxy of corruption level; human development index is used to represent welfare. Natural resource endowment and international trade are included in analysis to control robustness of corruption. The results show that corruption has negative impact on welfare. The impact in low-income countries is more destructive. Natural resource endowment and trade also have significant impacts, particularly for low-income countries. Since the corruption is destructive, government should eradicate corruption using preventive and repressive actions. Keywords:Economic development, corruption, low income countries, human development indexJEL classification numbers: D73, D31, I31AbstrakKajian ini bertujuan untuk mengukur dampak korupsi pada kesejahteraan, dan untuk membandingkan besarnya dampak antara negara-negara berpenghasilan tinggi dan berpenghasilan rendah. Indeks persepsi korupsi digunakan sebagai proksi tingkat korupsi; indeks pembangunan manusia digunakan sebagai pendekatan kesejahteraan. Sumber daya alam dan perdagangan internasional dimasukkan dalam analisis untuk mengontrol kekuatan variabel korupsi. Hasil kajian menunjukkan bahwa korupsi berdampak negatif pada kesejahteraan. Dampak korupsi di negara-negara miskin lebih buruk dari pada di negara-negara kaya. Sumber daya alam dan perdagangan juga memiliki dampak yang signifikan, terutama untuk negara-negara miskin. Karena korupsi bersifat merusak, pemerintah harus memberantas korupsi menggunakan tindakan preventif maupun represif.Kata kunci: Pembangunan ekonomi, korupsi, negara berpenghasilan rendah, IPMJEL classification numbers: D73, D31, I31